Collective goods, collective futures in Asia - Sargeson, Sally (Asian capitalisms., 2002)
This edited collection explores issues surrounding the provision of collective goods within the context of post-crisis East and Southeast Asia. It includes case studies on Korea, Indonesia, China, Laos, Malaysia and Singapore among others.